A Novel Nonenzymatic Hydrogen Peroxide Sensor Based on Magnetic Core-Shell Fe3O4@C/Au Nanoparticle Nanocomposite - Xiao Ni; Mingwei Tian; Jun Sun; Xiaojun Chen (International Journal of Analytical Chemistry)
Fe3O4@C/Au nanoparticle (AuNP) nanocomposites were prepared through electrostatic adsorption of AuNPs onto PDDA-functionalized core/shell Fe3O4@C magnetic nanospheres, which had been synthesized by a facile solvothermal method. The morphology and composition of the nanocomposites were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), etc. Moreover, highly electrocatalytic activity to the reduction of hydrogen peroxide (H2O2) was also exhibited on the Fe3O4@C/AuNP-modified indium tin oxide (ITO) electrode. The effect of solution pH and the modification amount of Fe3O4@C/AuNPs on the performance of electrocatalytic H2O2 reduction was investigated. Under the optimal conditions, the catalytic current showed a linear relationship with the increase of H2O2 concentration in the range of 0.007–15 mM and a detection limit of 5 μM. The H2O2 sensor showed high selectivity for H2O2 detection, which could effectively resist the interference of ascorbic acid (AA), uric acid (UA), and citric acid (CA). Finally, the H2O2 sensor was used in the real fetal bovine serum to detect H2O2 and obtained satisfactory results with the recovery values ranging from 95.14 to 103.6%.